Visual-motor integration, visual perception, and fine motor coordination in a population of children with high levels of Fetal Alcohol Spectrum Disorder - Doney, R.; Lucas, B.; Watkins, R.; Tsang, T.; Sauer, K.; Howat, Peter; Latimer, J.; Fitzpatrick, J.; Oscar, J.; Carter, M.; Elliott, E. (Pergamon Press, 2016)
© 2016 Elsevier Ltd. Background: Visual-motor integration (VMI) skills are essential for successful academic performance, but to date no studies have assessed these skills in a population-based cohort of Australian Aboriginal children who, like many children in other remote, disadvantaged communities, consistently underperform academically. Furthermore, many children in remote areas of Australia have prenatal alcohol exposure (PAE) and Fetal Alcohol Spectrum Disorder (FASD), which are often associated with VMI deficits. Methods: VMI, visual perception, and fine motor coordination were assessed using The Beery-Buktenica Developmental Test of Visual-Motor Integration, including its associated subtests of Visual Perception and Fine Motor Coordination, in a cohort of predominantly Australian Aboriginal children (7.5-9.6 years, n = 108) in remote Western Australia to explore whether PAE adversely affected test performance. Cohort results were reported, and comparisons made between children i) without PAE; ii) with PAE (no FASD); and iii) FASD. The prevalence of moderate (=16th percentile) and severe (=2nd percentile) impairment was established. Results: Mean VMI scores were 'below average' (M = 87.8 ± 9.6), and visual perception scores were 'average' (M = 97.6 ± 12.5), with no differences between groups. Few children had severe VMI impairment (1.9%), but moderate impairment rates were high (47.2%). Children with FASD had significantly lower fine motor coordination scores and higher moderate impairment rates (M = 87.9 ± 12.5; 66.7%) than children without PAE (M = 95.1 ± 10.7; 23.3%) and PAE (no FASD) (M = 96.1 ± 10.9; 15.4%). Conclusions: Aboriginal children living in remote Western Australia have poor VMI skills regardless of PAE or FASD. Children with FASD additionally had fine motor coordination problems. VMI and fine motor coordination should be assessed in children with PAE, and included in FASD diagnostic assessments.